Analysis of In-P based 1.55?m electrically pumped vertical-external- cavity surface-emitting lasers - Yap D.F.W.; Low A.L.Y.; Koh S.P.; Tiong S.K. (2023)
In this paper, theoretical analysis of the In-P based 1.55?m electrically pumped vertical-external-cavity surface-emitting lasers is presented. Computational experimental results show that short-cavity VCSELs (vertical-cavity surface-emitting lasers) with weak external feedback exhibit an increase of 37% output power compared with the conventional VCSELs. In addition, with an optimized external feedback, the -3dB modulation bandwidth can be increased by approximately 5% and having a wider eye opening in a 40Gbits-1 transmission system. IOP Publishing Ltd.